Analysis of Biological Exposure Duration and Worker Characteristics on The Incidence of Covid-19 in Hospitals - Umi Rizkiyah; M. Riza Setiawan; Bintang Tatius N. (Nusantara Science and Technology Proceedings, 2024)
Background: Biological exposure is one of the potential hazards caused by microorganisms, bacteria, and viruses that can be found in the hospital environment. In addition, many factors can increase the risk of contracting COVID-19, namely the availability of personal protective equipment, workload, work period, work experience, job category, knowledge, education level, length of exposure to infected patients, previous medical history, and psychological factors. The duration of exposure to biological agents affects the occurrence of occupational diseases. Objective: To analyze the relationship between the duration of biological exposure and worker characteristics and the incidence of COVID-19 in hospitals. Methods: The study used an analytical observational method with a cross-sectional design conducted at Charlie Hospital, Kendal Regency. The study sample amounted to 60 people using a questionnaire as a research instrument. Results: There is a relationship between the duration of biological exposure and the incidence of COVID-19 at Charlie Hospital, and there is a relationship between the characteristics of knowledge, attitudes, practices, and histories of comorbid diseases at Charlie Hospital. Conclusion: At Charlie Hospital, there is a strong correlation between the occurrence of COVID-19 and knowledge, attitudes, and practices.